Розробка ландшафту для дослідження моделей тех нічного зору роботів - Багаєв, Д. О.; Юріна, М. О.; Солодов, В. Д.; Храмцов, П. В. (ХНУРЕ, 2025)
In modern robotics, machine vision is a key technology that allows autonomous systems to navigate in space, recognize objects, and make decisions based on visual information. Given the complexity of the real world, developing and testing such algorithms in a physical environment is costly and risky. Therefore, virtual environments are becoming a powerful tool for testing computer vision models in controlled conditions. This paper considers the creation of a landscape for further use in the creation of a computer vision projection. The scanning and generation will be carried out using robots that will be controlled remotely.
Keywords: розробка ландшафту; ландшафт